2017
DOI: 10.1021/acssuschemeng.7b02245
|View full text |Cite
|
Sign up to set email alerts
|

Waste Valorization Process: Sulfur Removal and Hematite Recovery from High Pressure Acid Leach Residue for Steelmaking

Abstract: The current study put the emphasis on developing a novel and environmentally friendly waste valorization process to refine hematite from the residue of the high-pressure acid leaching (HPAL) of nickel laterite ore. The developed process consists of an alkaline leaching step utilizing sodium hydroxide to reduce the sulfur impurity content in the HPAL residue. This novel process is very efficient as it can be run at room temperature in a significantly short residence time (10 min). The refined HPAL residue has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The main phase in the residue was found to be hematite (Fe 2 O 3 ), with small intensities of quartz (SiO 2 ) and alunite (KAl 3 (SO 4 ) 2 (OH) 6 ) also observed. This result is similar to the phases of HPAL residue from Vale’s nickel plant located near the Goro mine in the south of New Caledonia reported by Ang et al Furthermore, Lei et al reported that the main phases of HPAL residue from Indonesian limonite laterite are hematite, chromite, alunite, and aluminosilicate.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The main phase in the residue was found to be hematite (Fe 2 O 3 ), with small intensities of quartz (SiO 2 ) and alunite (KAl 3 (SO 4 ) 2 (OH) 6 ) also observed. This result is similar to the phases of HPAL residue from Vale’s nickel plant located near the Goro mine in the south of New Caledonia reported by Ang et al Furthermore, Lei et al reported that the main phases of HPAL residue from Indonesian limonite laterite are hematite, chromite, alunite, and aluminosilicate.…”
Section: Resultssupporting
confidence: 86%
“…The residue generated from the HPAL process contains significant amounts of iron (up to 50%), which can be further processed and recovered to become a raw material for iron and steelmaking . Recently, the HPAL residue was successfully converted into blast furnace charge for ironmaking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel resources are primarily divided into nickel oxide minerals and nickel sulfide minerals. From a worldwide perspective, nickel in oxidized ore accounts for 65%–70% of the total land-based nickel reserves. At present, the resources of nickel sulfide ore in the world are gradually being exhausted, and the global nickel demand will continue to grow at a high rate. The trend in the nickel industry is to obtain nickel from nickel laterite ore to fulfil market demand.…”
Section: Introductionmentioning
confidence: 99%